STRATEGY FOR IMPROVING QUALITY SERVICES IN STUDENT MANAGEMENT IN MADRASAH INSTITUTIONS - Zaini, Ahmadi; Rizquha, Ach (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research focuses on strategies to improve service quality in student management at madrasah institutions. The main objective of this study is to identify and evaluate methods and approaches that can be implemented to enhance the quality of services provided to students in madrasah. The research methods used include literature review, interviews with teaching staff and administrative personnel, and direct observation of the student management process. The results of the study indicate that the implementation of technology-based management systems, improving the competence of teaching staff through regular training, and developing varied and inclusive extracurricular programs are effective steps to enhance service quality. Additionally, active participation from students' parents in the educational process also significantly contributes to service improvement. This study concludes that integrated and sustainable strategies are essential to achieve optimal service quality improvement in student management at madrasah